Public R&D Support and Firms' Performance: A Panel Data Study - Øivind Anti Nilsen; Arvid Raknerud; Diana-Cristina Iancu (Institute of Labor Economics (IZA), 2018)
We analyse all the major sources of direct and indirect R&D subsidies in Norway in the period 2002-2013 and compare their effects on individual firms' performance. Firms that received support are matched with a control group of firms that did not receive support using a combination of stratification and propensity score matching. Changes in performance indicators before and after support in the treatment group are compared with contemporaneous changes in the control group. We find that the average effects of R&D support among those who obtained grants and/or subsidies are positive and significant in terms of performance indicators related to economic growth: value added, sales revenue and number of employees. The estimated effects are larger for start-up firms than incumbent firms when the effects are measured as relative effects (in percentage points), but smaller when these effects are translated into level effects. Finally, we do not find positive effects on return to total assets or productivity for firms who received support compared with the control group.
Keywords: C33; C52; D24; O38; 330; public policy; firm performance; treatment effects; stratification; propensity score matching; productivity